Survey of six bee viruses using RT-PCR in Northern Thailand - Sirikarn Sanpa (2018)
Six honey bee viruses were surveyed using RT-PCR in Northern Thailand where about 80% of Thai apiaries are located. Tested samples were found to be positive for deformed wing virus (DWV), acute bee paralysis virus (ABPV), sacbrood virus (SBV) and Kashmir bee virus (KBV). In the collected samples, neither chronic bee paralysis virus nor black queen cell virus nucleic acids could be detected. It was found that DWV was the most widespread and ABPV was the second most prevalent. Kashmir bee virus was found only in the Lampang province where high infestation of Varroa destructor mite occurred. Tropilaelaps, European foulbrood, and Chalkbrood diseases were found in some apiaries. © 2008 Elsevier Inc. All rights reserved.